Convex quadratic relaxations for mixed-integer nonlinear programs in power systems - Hijazi, Hassan; Coffrin, Carleton; Hentenryck, Pascal Van (Mathematical programming computation, 2017)
This paper presents a set of new convex quadratic relaxations for nonlinear and mixed-integer nonlinear programs arising in power systems. The considered models are motivated by hybrid discrete/continuous applications where existing approximations do not provide optimality guarantees. The new relaxations offer computational efficiency along with minimal optimality gaps, providing an interesting alternative to state-of-the-art semidefinite programming relaxations. Three case studies in optimal power flow, optimal transmission switching and capacitor placement demonstrate the benefits of the new relaxations.